Biosynthesis of astaxanthin in tobacco leaves by transplastomic engineering - Hasunuma, Tomohisa; Miyazawa, Shin‐Ichi; Yoshimura, Satomi; Shinzaki, Yuki; Tomizawa, Ken‐Ichi; Shindo, Kazutoshi; Choi, Seon‐Kang; Misawa, Norihiko; Miyake, Chikahiro (The Plant journal : for cell and molecular biology, 2008)
Summary The natural pigment astaxanthin has attracted much attention because of its beneficial effects on human health, despite its expensive market price. In order to produce astaxanthin, transgenic plants have so far been generated through conventional genetic engineering of Agrobacterium‐mediated gene transfer. The results of trials have revealed that the method is far from practicable because of low yields, i.e. instead of astaxanthin, large quantities of the astaxanthin intermediates, including ketocarotenoids, accumulated in the transgenic plants. In the present study, we have overcome this problem, and have succeeded in producing more than 0.5% (dry weight) astaxanthin (more than 70% of total caroteniods) in tobacco leaves, which turns their green color to reddish brown, by expressing both genes encoding CrtW (β‐carotene ketolase) and CrtZ (β‐carotene hydroxylase) from a marine bacterium Brevundimonas sp., strain SD212, in the chloroplasts. Moreover, the total carotenoid content in the transplastomic tobacco plants was 2.1‐fold higher than that of wild‐type tobacco. The tobacco transformants also synthesized a novel carotenoid 4‐ketoantheraxanthin. There was no significant difference in the size of the aerial part of the plant between the transformants and wild‐type plants at the final stage of their growth. The photosynthesis rate of the transformants was also found to be similar to that of wild‐type plants under ambient CO2 concentrations of 1500 μmol photons m−2 s−1 light intensity.